Opportunist infections in patients with Crohn's Disease and Ulcerative Colitis: A current integrative review (Research, Society and Development, 2025)
Objectives: Conduct a literature review on the most common opportunistic infections in patients with Crohn's Disease and Ulcerative Colitis. Methodology: This research focuses on an integrated literature review. The integrative review (IR) method allows for a greater sense of understanding by employing a systematic and rigorous process. Results: Thus, a total of 13 articles were discovered in the VHL database, while 42 papers were discovered in the Medline database via PubMed, totaling 55 publications. The final sample consisted of 8 articles, all belonging to the Medline database via PubMed after applying the inclusion and exclusion criteria. Conclusion: It is considered extremely important to examine all available evidence on occult infections in patients with Crohn's disease and ulcerative colitis, as it will allow patients and the health professionals who care for them to respond and act appropriately in order to preserve their quality of life and ensure that their treatments are effective.